2008
DOI: 10.1080/09595230701710852
|View full text |Cite
|
Sign up to set email alerts
|

Dispensing opioid substitution treatment: practices, attitudes and intentions of community‐based pharmacists

Abstract: Introduction and Aims. Community-based pharmacists (CPs) play a pivotal role in the provision of opioid substitution treatment (OST). This study examined practices, experiences, attitudes and intentions of a sample of South Australian pharmacists involved with the provision of OST. Design and Methods. A random sample, stratified by geographic location, of 50 SA CPs were administered a telephone survey. The survey included pharmacist and pharmacy details, current practices, problems experienced, attitudes towar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 5 publications
(3 reference statements)
3
35
2
Order By: Relevance
“…A Victorian report into the impact of dispensing fees on OST patients reported a number of dire circumstances for patients with limited capacity pay; these included prioritising dispensing fees over other necessities, reliance on emergency relief services, and in some cases engagement in sex work or acquisitive crime in order to make the payment. 38 Indeed dispensing fees were identified as a primary reason for treatment discontinuation. The report identified that patients' difficulties in paying the dispensing fees was a key contributor for breakdowns in the patientpharmacist relationship.…”
Section: Provision Of Opioid Substitution Therapy Services In Australmentioning
confidence: 99%
See 1 more Smart Citation
“…A Victorian report into the impact of dispensing fees on OST patients reported a number of dire circumstances for patients with limited capacity pay; these included prioritising dispensing fees over other necessities, reliance on emergency relief services, and in some cases engagement in sex work or acquisitive crime in order to make the payment. 38 Indeed dispensing fees were identified as a primary reason for treatment discontinuation. The report identified that patients' difficulties in paying the dispensing fees was a key contributor for breakdowns in the patientpharmacist relationship.…”
Section: Provision Of Opioid Substitution Therapy Services In Australmentioning
confidence: 99%
“…The author of the report, Rowe (2008), argued that dispensing subsidised by the Commonwealth-regulated Schedule of Pharmaceutical Benefits would potentially increase the number of pharmacists willing to dispense OST as the risk of bad debt associated with the programme would be reduced. 38 Other cost-saving opportunities arise with new OST regimens, such as the new buprenorphine-naloxone regimen which involves a larger number of unsupervised and take-away doses. Yet despite this, Winstock and colleagues (2007) found that in NSW pharmacies, OST dispensing charges differed little across the different regimens and with little difference between daily methadone dosing and buprenorphinenaloxone dosing.…”
Section: Provision Of Opioid Substitution Therapy Services In Australmentioning
confidence: 99%
“…Several studies have examined the knowledge and attitudes of practising pharmacists, but there have been no studies in a pharmacy student population. Additionally, current OST education practices and their potential affect on professional knowledge and attitudes have been reported .…”
Section: Discussionmentioning
confidence: 99%
“…In studies looking at client concerns with OST, discriminatory treatment by pharmacy staff was a common complaint . The number of OST clients per pharmacy is directly related to the number of negative issues experienced . Only 50% of individuals who identify as heroin users are currently accessing OST .…”
Section: Introductionmentioning
confidence: 99%
“…This important responsibility may integrate pharmacists more into the health care system for drug users. Some previous studies have already shown that pharmacists appear to be in favour of providing OMT, supervising intake [43] and playing an important role in treatment delivery, including referring difficult patients to other services [44]. This potentially enhanced role for pharmacists is a unique opportunity to develop and improve the harm reduction network through the training of pharmacists.…”
Section: Discussionmentioning
confidence: 99%